STATISTICAL MODEL FOR ESTIMATING N-P-K DEPOSITION FROM PRECIPITATION IN AGROECOSYSTEMS OF THE BRAZILIAN SEMI-ARID REGION - Pérez-Marin, Aldrin Martin; Silva, Fernando Moreira da; Costa Júnior, Djailson Silva da; Silva, Bruce Kelly da Nobrega; Cunha, John Elton de Brito Leite; Menezes, Rômulo Simões Cezar (Floresta, 2024)
The objective of the study was to adjust a linear statistical model to estimate the input of N, P, and K, through rainfall, in agroecosystems in the Agreste region of Paraíba. The data for the parameterization of the model were obtained in a field experiment conducted in the municipality of Esperança, Paraíba, from January to December. Descriptive, inferential and probabilistic statistics were used for the methodological development of this study. The equations obtained by the linear model can be used to estimate nutrient deposition through rainfall in climatic conditions similar to those of the region under study. The need for comparative studies with other production systems practiced in the region must be highlighted, to validate the data and the model.